Precision crop management for indoor farming - Sabri, Fatin Nadia; Mohamad Hanif, Noor Hazrin Hany; Janin, Zuriati (IEEE, 2019)
This paper offers a method to manage crops for indoor farming which is focused on providing the crops a precise amount of water, ambient temperature and humidity. The proposed method utilizes six soil moisture sensors that are placed in the soil around the crops, and the source of water is mounted above the plants. The water pump was repeatedly tested at different configurations to determine the optimum flow rate and pressure of the water supply. The saturation point of the soil under investigation was also identified to precisely control the amount of water supplied to the plants. The advantage of this crop management system is that it could be remotely monitored using IoT (Internet of Things). The outcome of this work shows optimistic possibility of managing indoor farming in precise conditions to yield optimum production of crops.